Tropical Fruits, (2nd Edition): Volume II - Paull, Robert E (CABI, 2014)
Soursop is the most tropical of and produces the largest fruit among the Annona species. The Caribbean is the area of origin, although soursop was distributed very early to the warm lowlands of eastern and western Africa and to south-east China. It is commonly found on subsistence farms in south-east Asia, and was established very early in the Paciﬁ c islands. Soursop is considered well suited to processing and for use in local markets for fresh consumption. It is grown extensively in Mexico, from Culiacan to Chiapas, and from Veracruz to the Yucatan Peninsula in the Gulf region. Large orchards are seen in this region, with a total of more than 6000 ha being grown. Venezuela has around 4000 ha, Brazil more than 2000 ha and Peru almost 500 ha. Colombia and Ecuador have also developed some modern orchards in the last few years for the local fruit markets and for industrial use. Exports of fresh fruit are very low. Rollinia originated in the forests of the Brazilian Amazon in the states of Acre, Rondônia and the Antilles. It has been spread throughout Brazil and other South American countries, as well as Florida (Manica, 2000; Donadio et al., 2002). This species, apparently cultivated since pre-Columbian times, is not widely cultivated for commercial purposes; rather, it occurs in backyard orchards or small plantings.